Complications in hospitalized patients with SARS-CoV2 infection - de Souza Borges Tavares , Marco Antônio; Bisinotto Skaff , Gabriela; Gomes Fredrich, Isadora Martins; Nery Ayach, Mariana; Quarti Vieira, Isabela Anuda; Martins Bertoncelo, Beatriz; Fernanda dos Santos , Tauanne; Dresch, Henrique; Kato da Silva, Baldomero Antônio; Costa Marques, Mariana; Vieira , Brenda; Alves Dias, Robson Vinícius (Brazilian Journal of Implantology and Health Sciences, 2023)
OBJECTIVES: The present study aimed to assess the prevalence of complications during hospitalization in patients diagnosed with COVID-19, as well as the association with mortality and prognosis. METHODS: A retrospective cohort study involved 306 patients admitted to a COVID ward and ICU aged 18 years or older with confirmed SARS-CoV2 infection admitted to a Brazilian Tertiary Hospital. Demographic, clinical, biochemical, radiological and outcome data were collected from the patients’ charts. RESULTS: According to the data analyzed during hospitalization, 230 (75.2%) patients developed complications, 281 (91.8%) patients had comorbidities and 169 (55.2%) patients died. There are no differences regarding the sex of the patients. The most prevalent complication was ventilator-associated pneumonia, present in 130 (42.5%) patients, followed by acute kidney injury or chronic kidney disease requiring hemodialysis, presented by 100 (32.7%) patients. The calculation of the relative risk of death according to the occurrence of complications showed p<0.0001 for acute renal failure, p<0.0001 for orotracheal intubation and p=0.0434 for acute myocardial infarction. CONCLUSION: The relative risk of death in COVID-19 is significant, showing an increase in relation to age, length of hospital stay and complications. Prevention, early diagnosis and appropriate treatment are essential to reduce the mortality rate in patients with SARS-CoV-2 infection.